Arylation of allylphosphonates and application to the preparation of phosphonomethyl-coumarin, -quinolinone and -benzoxepinone skeletons. Issue 13 (25th March 2015) - Abdelli, Abderrahmen; Gaucher, Anne; Efrit, Mohamed Lotfi; M'rabet, Hedi; Prim, Damien
Graphical abstract: Abstract: An efficient and selective synthesis of Z -(het)arylallylphosphonates is described. The versatile Pd-assisted process also allowed polyarylation sequences leading to star-shaped and binaphthyl derivatives. The methodology could be extended to the preparation of new phosphonomethyl-coumarin, -quinolinone, and -benzoxepinone architectures in high yields.